Formulasi minuman sinbiotik dengan okara (Glycine max) dan probiotik Lactiplantibacillus plantarum Dad-13 - Suplig, Angelina Christine; Agung Yogeswara, Ida Bagus; Kusumaningsih, Purwaningtyas; Puspaningrum, Dylla Hanggaeni Dyah (Poltekkes Kemenkes Aceh, 2024)
Background: Okara is the byproduct of soymilk production process. Okara contains high nutritional value and considered as a source of oligosaccharide. Oligosaccharide in okara will stimulate the growth of probiotic bacteria and thus showed prebiotic effect. The underutilization of goat milk can be used as a carrier for probiotic bacteria as well as to develop sinbiotic functional foods.Objective: This study aims to determine the formulation of fermented goat's milk with the addition of okara (glycine max) as a synbiotic drink to obtain dietary fibre, amino acid profiles as well as microbiology and sensory profiles.Methods: Randomized complete designed were used in this study with 5 formulations with the addition of okara. The study was conducted in Laboratorium Sains Dasar Universitas Dhyana Pura in July of 2023. The okara was obtained at local tofu producer in Denpasar, whereas goat milk was obtained from milk distributor located in Denpasar. The populations of this study were okara and goat milk that already thoroughly cleaned and pasteurised. Data collection was performed in the laboratory and all data were analyzed using Anova and Duncan with significant levels of 95%.Results: The study showed that the addition of 5% okara (F4) (Glycine max) was the most prefarable symbiotic drink. Based on proximate analysis, the F4 contained water 88.58%, fat 1.11%, protein 2.17%, carbohydrate 7.656%, total LAB 5.05 x 108 CFU/ mL, essential amino acids, and 2.19% dietary fiber. Based on sensory tests, formulation 1 (0%) and formulation 4 (5%) had overall significant differences.Conclusion: The addition of okara 5% with goat's milk can be used as a synbiotic drink. The formulation with the addition of 0% okara and 5% okara have overall significant differences in terms of taste, texture, aroma and also color.